2021
DOI: 10.3324/haematol.2021.279248
|View full text |Cite
|
Sign up to set email alerts
|

Combined transcriptome and proteome profiling of SRC kinase activity in healthy and E527K defective megakaryocytes

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…They found that MKs differentially express mRNAs for MMPs and TIMPs, and only a subset of these are transferred to platelets. Human iPSC-derived MKs [ 62 ], CD34+ HSC-derived MKs [ 63 ] and imMKCL [ 64 , 65 ] have all been used for bulk RNA-seq studies, while similar studies have not yet been performed for primary MKs because of their low yield and the difficulty extracting them from the bone marrow. A comparison between the different types of in vitro MKs using RNA-seq datasets has not been reported.…”
Section: Bulk Transcriptomics Of Healthy Megakaryocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that MKs differentially express mRNAs for MMPs and TIMPs, and only a subset of these are transferred to platelets. Human iPSC-derived MKs [ 62 ], CD34+ HSC-derived MKs [ 63 ] and imMKCL [ 64 , 65 ] have all been used for bulk RNA-seq studies, while similar studies have not yet been performed for primary MKs because of their low yield and the difficulty extracting them from the bone marrow. A comparison between the different types of in vitro MKs using RNA-seq datasets has not been reported.…”
Section: Bulk Transcriptomics Of Healthy Megakaryocytesmentioning
confidence: 99%
“…Significant minor intron retention was detected in the patient transcriptomes for 354 MK genes, including many linked to the thrombocytopenia phenotype of platelets. Lentiviral-transduced CD34+ HSCs were generated for wild-type SRC and E527K-SRC and differentiated into MKs before applying bulk RNA-seq [ 63 ]. The E527K SRC variant causes thrombocytopenia, and MK transcriptomes for this variant showed 852 significant differentially expressed genes, with interferon I signaling as the most interesting pathway after confirmation with MK proteomics.…”
Section: Platelet and Megakaryocyte Transcriptome To Decipher Inherit...mentioning
confidence: 99%
See 1 more Smart Citation